If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 = -3(5 + -1x) + 3(4x + -2) Reorder the terms: 4 + x = -3(5 + -1x) + 3(4x + -2) 4 + x = (5 * -3 + -1x * -3) + 3(4x + -2) 4 + x = (-15 + 3x) + 3(4x + -2) Reorder the terms: 4 + x = -15 + 3x + 3(-2 + 4x) 4 + x = -15 + 3x + (-2 * 3 + 4x * 3) 4 + x = -15 + 3x + (-6 + 12x) Reorder the terms: 4 + x = -15 + -6 + 3x + 12x Combine like terms: -15 + -6 = -21 4 + x = -21 + 3x + 12x Combine like terms: 3x + 12x = 15x 4 + x = -21 + 15x Solving 4 + x = -21 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + x + -15x = -21 + 15x + -15x Combine like terms: x + -15x = -14x 4 + -14x = -21 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + -14x = -21 + 0 4 + -14x = -21 Add '-4' to each side of the equation. 4 + -4 + -14x = -21 + -4 Combine like terms: 4 + -4 = 0 0 + -14x = -21 + -4 -14x = -21 + -4 Combine like terms: -21 + -4 = -25 -14x = -25 Divide each side by '-14'. x = 1.785714286 Simplifying x = 1.785714286
| 2log(x+2)-log(5x+6)=0 | | 2/5=3.8/x | | 16x+7y=204 | | -5(4a-7)=-6n-35 | | 3y+8v=53 | | 1/2=x/4.2 | | (x+7)+(x-1)= | | x/3=42/63 | | 0=-x^4+2x^3+4x^2-8x | | x-1-2(x-5)=2(3x-2) | | 4(2.5d+4)+3(2d-3)= | | x/5=15/40 | | 4.2-1.4=2.1 | | 5/8=40/x | | 3.61n=4+2.247n | | -6x=4x+1 | | 6x-2=2x+8*2 | | 2(3.5Z+2)-(3+5z)= | | 24=3(m-1)-4(m-6) | | 5=-7a+5a | | X-2+4x+10+3y=180 | | 20m+30=40m-10 | | 4(x+4)=6x+20 | | 3/10=x/75 | | 7y-2(y-3)=29 | | 3x-2+x+71=180 | | 5+4=2019 | | 2-4t=3t-19 | | 2x-16+1=x | | 3x^3-x^2-30x+10=0 | | 6/7m=36/49 | | 12x-13x= |